Contaminated Heavy Metals in Rice of Surin Province, Thailand - Kheangkhun, Napaporn; Sringam, Jutamart; Kumpinit, Waraporn; Wattanakornsiri, Amnauy; Phuengphai, Pongthipun (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 1 (2020): January - March 2020DO - 10.14456/nujst.2020.6, 2020)
The purposes of this research were to investigate the types and quantities of contaminated heavy metals in rice, and to compare the heavy metals contaminated in jasmine rice, black rice and germinated brown rice in Surin province, Thailand, with the total of 15 rice samples. The experiment was performed using atomic absorption spectroscopy technique. The results showed that all rice samples had the amount of chromium in the range of 0.248-0.660 mg/kg. However, the detected amounts did not exceed the highest standard of chromium in cereal agricultural products according to the national standards of People's Republic of China defined as 1.00 mg/kg. In addition, the amount of lead in the samples was not found, which the highest standard of lead given by European Communities and Food Standard Australia and New Zealand was defined as not more than 0.2 mg/kg. Therefore, all the rice samples used in this research were considered at safety level for consumption. This basic information is useful for consumers taking consideration to consume rice of Surin province safely. Keywords: Jasmine rice, Black rice, Germinated brown rice, Heavy metal